Development and verification of yield surfaces for I-sections - Shoaib, Afaq (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2009)
In the design of many building structures for ultimate states the use of interaction equations is quite common. Despite this there is still a need for more advanced and flexible equations which consider all forces in space. Steel l-section members are often employed as beam and column elements for both structural and aesthetic reasons. The purpose of this thesis is to develop, in principle, the interaction equations for l-sections and verify it using experimental and finite element techniques. Two types of interaction equations are developed. One is the approximate approach in which single equation interaction equation is developed for biaxial bending moment and bimoment. The yield surface developed based on this approach fills the large gap in the previously developed yield surface. Second is the exact solution in which interaction equations for biaxial bending, biaxial shear, axial force, uniform torsion and bimoment are developed. This exact solution results in an improved, closed, continuous and convexed yield surface for an l-section. These two types of interaction equations are verified using a series of experiments and numerically using finite element analysis using software LUSAS.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin.